2017
DOI: 10.1007/s00330-017-4831-y
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of 18F-FDG PET/CT in predicting the pathological response to neoadjuvant chemotherapy in patients with breast cancer: a meta-analysis and systematic review

Abstract: • This meta-analysis assesses the role of PET/CT in breast cancer during NAC. • Pathological responses were based on both primary tumour and lymph node. • F-FDG PET/CT has a moderate accuracy in predicting the pathological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 56 publications
0
60
1
Order By: Relevance
“…To date, three main methods were reported for early response assessment in neoadjuvant treatment of breast cancer: 18 F-FDG PET/CT, dynamic contrast enhanced MRI (DCE-MRI), and ultrasound 9 , 15 , 16 . Meta-analysis showed that 18 F-FDG PET/CT had a moderate accuracy for the early prediction for pCR (sensitivity 85%, specificity 79% and diagnostic odds ratio 21.8), especially in HER2 positive and triple negative breast cancer 16 , 17 . DCE-MRI was also an effective method for early monitoring the efficacy during NAT (sensitivity 87%, specificity 82% and diagnostic odds ratio 30.3) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, three main methods were reported for early response assessment in neoadjuvant treatment of breast cancer: 18 F-FDG PET/CT, dynamic contrast enhanced MRI (DCE-MRI), and ultrasound 9 , 15 , 16 . Meta-analysis showed that 18 F-FDG PET/CT had a moderate accuracy for the early prediction for pCR (sensitivity 85%, specificity 79% and diagnostic odds ratio 21.8), especially in HER2 positive and triple negative breast cancer 16 , 17 . DCE-MRI was also an effective method for early monitoring the efficacy during NAT (sensitivity 87%, specificity 82% and diagnostic odds ratio 30.3) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic analysis, the sensitivity of MRI was shown to be superior to that of other diagnostic modalities, with the exception of PET–CT. On the other hand, meta‐analytical data suggested that PET–CT yields moderate accuracy in the identification of patients who will have a pCR. However, recent results suggested that PET–CT and integrated metabolic radiomics may have prognostic value for Ki‐67 expression, response to NAT, as well as local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Breast MRI is commonly used to assess the disease response to NAT but is known to overestimate residual disease 29 , especially when a pCR has been achieved 30 , and could potentially result in higher rates of mastectomy, as in the setting of upfront surgery 31 . In a systematic analysis 32 , the sensitivity of MRI was shown to be superior to that of other diagnostic modalities, with the exception of PET-CT. On the other hand, meta-analytical data suggested that PET-CT yields moderate accuracy in the identification of patients who will have a pCR 33 . However, recent results 34 suggested that PET-CT and integrated metabolic radiomics may have prognostic value for Ki-67 expression, response to NAT, as well as local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased glucose metabolism within breast cancer tissue on 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) is a useful indicator to assess the effectiveness of NAC [ 6 ]. Several meta-analyses have reported that 18 F-FDG PET/CT scans performed during or after NAC could predict the final pathological response after completion of NAC [ 7 10 ]. A meta-analysis directly comparing PET/CT and breast MRI reported that PET/CT has a higher sensitivity and specificity for assessment of pathological response than conventional MRI when performed before 3 cycles of NAC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%